INFLUENCE OF PHYSICAL QUALITIES ON THE EFFICIENCY OF COMPETITIVE ACTIVITY OF FREESTYLE WRESTLERS - Kuvanov, V.A.; Mikhailovsky, S.P.; Agaev, R.A.; Davydov, M.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to establish the dependence of the success of competitive activity on the level of development of the physical qualities of student freestyle wrestlers. Methods and structure of the study. 112 students from four universities of St. Petersburg involved in freestyle wrestling took part in the scientific experiment. The following scientific methods were used in the work: theoretical analysis and generalization of data from special scientific and methodological literature, questioning, pedagogical observation (stenography, timing of fights and training sessions), testing, instrumental methods for assessing various aspects of readiness, methods of mathematical statistics. Results and conclusions. The conducted correlation analysis made it possible to determine a group of indicators of special physical fitness, which largely determine the success of the competitive activity of student freestyle wrestlers. This complex included indicators of the quantity, quality and time of throws in special tests.